Effects of high-intensity interval training on selected indicators of physical fitness among male team-sport athletes: a systematic review and meta-analysis - Yuan, Yandong; Soh, Kim Geok; Qi, Fengmeng; Bashir, Marrium; Zhao, Ningxia (Public Library of Science, 2024)
Background Superior physical fitness and performance are essential in male team sports. Among a myriad of training methodologies, high-intensity interval training (HIIT) has gained popularity owing to its unparalleled efficiency and effectiveness. Previous studies have established that HIIT is a proven and effective approach for enhancing various physiological performance outcomes, particularly oxygen consumption capacity, in individual sports. Despite potential differences in training practices between male and female athletes, HIIT is recognized as an anaerobic training approach for team-sport athletes. This systematic review aimed to comprehensively and innovatively analyze the existing literature to examine the effectiveness of HIIT on oxygen consumption performance among male team-sport athletes. Methods A comprehensive literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines across the PubMed, SCOPUS, Web of Science, and SPORTDiscus databases until December 31, 2023. The inclusion criteria for this review encompassed research articles published in peer-reviewed journals that specifically focused on the impact of HIIT on the oxygen consumption performance of male players engaged in team sports. The study population exclusively consisted of male participants. The collected data included study characteristics, participant demographics, intervention details, and outcomes. Methodological quality assessment was performed using standardized criteria. The effect sizes (ESs) were calculated, and a meta-analysis was conducted using a random-effects model. Results The literature search yielded 13 eligible studies encompassing 286 athletes aged 14–26 years. The meta-analysis showed statistically significant enhancements in maximal oxygen uptake (VO2max) in six studies (ES, 0.19−0.74; p < 0.005), Yo-Yo Intermittent Recovery Test (YYIRT) performance in six studies (ES, 0.20−2.07; p = 0.009), repeated-sprint ability total time (RSAtotal) in five studies (ES, 0.18−1.33; p < 0.001), and the best and average times for repeated-sprint ability (RSAbest and RSAmean, respectively) in four studies (ES, 0.47−1.50; p < 0.001). However, two studies did not report any significant differences in the outcomes of the Velocity in 30–15 Intermittent Fitness Test (VIFT) between the experimental and control groups (ES, −0.08 and −0.27; p = 0.87 and 0.443, respectively). Moreover, one study did not report any significant differences in the maximal aerobic speed (MAS) (ES, 0.41, p = 0.403). Conclusions HIIT significantly improved VO2max, YYIRT, and RSA; however, it did not appear to enhance VIFT and MAS performance, irrespective of age or competition level. These findings indicate that HIIT could serve as a valuable method for improving oxygen consumption performance (VO2max, YYIRT, and RSA) in male team-sport athletes, offering a time-efficient alternative to the traditional training methods. Further research is warranted to investigate its impact on performance outcomes in competitive settings and identify optimal HIIT protocols tailored to specific team sports.